PEMBELAJARAN TERPADU BERBASIS KARAKTER ISLAMI PADA PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN (PPKn) - Henni Yusda Rahmiyanti; Sri Mariamah Dalimunthe (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2020)
This study tries to make a systematic picture of how Integrated Learning Based on Islamic Character in Subjects of Civic Education (PPKn). With the location of the research in SMA Negeri 1 Mandastana, Barito Kuala Regency. The role of the teacher as: 1) a catalyst, the role model of a teacher is an absolute factor in the development of effective character education for students, because of their position as figures or idols imitated by students. 2) Inspirator means a teacher must be able to arouse students' enthusiasm to progress to develop their potential. 3) motivator, meaning that every teacher must be able to awaken the spirit, work ethic and extraordinary potential of students themselves. 4) dynamic, meaning each teacher has the ability to push students towards the achievement of goals with wisdom, patience, workmanlike, intelligent and upholds spirituality. 5). evaluator, means that every teacher is required to be able and always evaluate their attitudes or behaviors, and the learning methods used in the development of student character education, so that the level of effectiveness, efficiency and productivity of the program can be known. Thus it can be concluded that in the context of the education system in schools to develop Islamic character based education for students, teachers must be positioned or positioned themselves in the true nature, namely as instructors and educators, which means that in addition to transferring knowledge, it also educates and develops the participant's personality. students through the intractions they do in the classroom and outside the classroom.